2020
DOI: 10.1002/job.2475
|View full text |Cite
|
Sign up to set email alerts
|

Financial inadequacy and the disadvantageous changes in time perspective and goal‐striving strategies throughout life

Abstract: Summary As inequality in wealth and income continues to grow, it is important to consider the implications of financial disparities for worker motivation and behavior. While workers with socioeconomic disadvantages have a decreased chance of career success and upward social mobility, the potential mechanisms linking financial status to work motivation outcomes are not fully known. Drawing on theory on resource scarcity, we address this issue and propose that financial inadequacy shapes the extent to which work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…Meuris & Leana (2015) provide an extensive review of the scarcity literature, explaining how scarcity might lead to differences in outcomes such as job performance, burnout, withdrawal, workplace safety, and knowledge attainment. Although some OP/OB research has begun to apply Scarcity Theory (e.g., Sayre 2023, Wang & Ford 2020, it deserves greater attention in economic stress scholarship.…”
Section: Financial Deprivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Meuris & Leana (2015) provide an extensive review of the scarcity literature, explaining how scarcity might lead to differences in outcomes such as job performance, burnout, withdrawal, workplace safety, and knowledge attainment. Although some OP/OB research has begun to apply Scarcity Theory (e.g., Sayre 2023, Wang & Ford 2020, it deserves greater attention in economic stress scholarship.…”
Section: Financial Deprivationmentioning
confidence: 99%
“…Much of this research does not explicitly focus on employee populations, although most of it does focus on adults who are typically working. Research on work-specific outcomes is sparse, although studies have linked financial stress to outcomes such as increased absenteeism and decreased organizational commitment (Kim & Garman 2003), motivational challenges (Wang & Ford 2020), decreased job satisfaction and increased burnout (Munyon et al 2020), increased work-family conflict (Lawrence et al 2013), and increased turnover (Adams et al…”
Section: Financial Stressmentioning
confidence: 99%
“…Earnings from gainful employment represent an essential factor in meeting the household’s needs and fulfilling important life opportunities. Research has shown that working poverty is associated with a low standard of living and perceived economic uncertainties that negatively impact individual life course choices and one’s own aspirations to invest in long-term goals [ 1 , 2 ]. International studies from the field of public health, epidemiology, and occupational health research further indicate that employees with an income below the poverty line suffer from various detrimental health outcomes and behaviors [ 3 ], including poor self-rated health [ 4 , 5 ], mental disorders [ 6 9 ], obesity [ 10 ], smoking [ 11 , 12 ], alcohol consumption [ 13 ], and mortality [ 14 ].…”
Section: Introductionmentioning
confidence: 99%